New approach for the clinical monitoring of 25‐hydroxyvitamin D3 and 25‐hydroxyvitamin D2 by ultra high performance liquid chromatography with MS/MS based on the standard reference material 972. Issue 23 (27th October 2013) - Plíšek, Jiří; Krčmová, Lenka Kujovská; Aufartová, Jana; Morales, Tanausú V.; Esponda, Sarah M.; Oros, Roman; Kasalová, Eva; Santana‐Rodriguez, Jose J.; Sobotka, Luboš; Solich, Petr; Solichová, Dagmar
<x xml:space="preserve">Abstract</x> Biomarkers, 25‐hydroxyvitamin D3 and 25‐hydroxyvitamin D2, are important indicators of the vitamin D general status and are monitored in several pathophysiological disorders, such as osteoporosis, diabetes, heart disease, etc. A novel ultra‐HPLC with MS/MS methodology for the analysis of 25‐hydroxyvitamin D derivatives coupled with a very simple and highly rapid sample preparation step was developed. Analytical parameters obtained showed linearity (R2) above 0.999 for both vitamins with accuracies between 95.8 and 102%. The LODs were as low as 0.22 and 0.67 nmol/L for 25‐hydroxyvitamin D3 and 25‐hydroxyvitamin D2, respectively. Intra‐assay precision (%RSD) was lower than 4.5%, and inter‐assay precision (%RSD) was lower than 6.5%. The feasibility of the developed methodology to be applied in clinical routine analysis has been proved by its application in blood samples from non‐agenarian patients, patients with familial hypercholesterolemia and patients suffering from age‐related macular degeneration.